The Influence of Marketing Mix and Services Quality that Influencing the Success of 4-stars Resort Business in Saraburi Province - Yailumyong, Jeeranun (Journal of Management Science Nakhon Pathom Rajabhat University, 2023)
This research aimed to 1) investigate the variables of marketing mix, service quality, and the success of 4-star resort businesses in Saraburi province, and 2) investigate the effect of marketing mix and service quality on the success of 4-star resort businesses in Saraburi province. This research is designed to be quantitative. 384 clients that utilize the service. The study's findings revealed that (1) marketing mix variables, service quality factors, and the success of the 4-star resort company in Saraburi Province were all rated highly. (2) Factors affecting the success of the 4-star resort business in Saraburi Province, it was found that in terms of products and services marketing, promotion, process, physical evidence, attending to service consumers' requirements, providing service users with assurance Additionally, there is statistically substantial evidence that consumer comprehension impacts the success of the 4-star resort industry in the province of Saraburi Article history: Received 14 June 2022 Revised 22 August 2022 Accepted 22 August 2022 SIMILARITY INDEX = 3.35 %